Perception Of Implementing The Implementation of Nurse Nursing Care of Social Isolation PNPM Program - Retty Octi Syafrini; Budi Anna Keliat; Yossie Susanti Eka Putri (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2020)
One of the activities in the Professional Nursing Practice Model (PNPM) Life is giving nursing care aimed at improving nursing services. This study aims to determine how perceptions of nurses toward the implementation of nursing care in the social isolation Soul PNPM program. The study design was conducted using qualitative methods with phenomenological approach. Data collection was performed at 7 nurses who have been trained PNPM Soul with in-depth interviews. The results showed four themes related to sustainability implementation of social isolation nursing care that benefits the implementation of nursing care and the role of social isolation and nursing staff in the implementation of social isolation. Conscious social isolation nursing care nurses can provide better benefits for nursing services and patient and family, so it is recommended to the hospital to increase its involvement in maintaining the sustainability of social isolation implementation of nursing care.